2022
DOI: 10.3390/w14071078
|View full text |Cite
|
Sign up to set email alerts
|

Biological Layer in Household Slow Sand Filters: Characterization and Evaluation of the Impact on Systems Efficiency

Abstract: Schmutzdecke, the biofilm formed on the top of the sand bed in household slow sand filters (HSSF) is a key factor for the filters’ high efficiency in removing particles and microorganisms from water. This paper aims to investigate the extracellular polymeric substances composition (carbohydrates and proteins), biomass, dissolved oxygen, and microbial community in two types of HSSFs and identify a correlation between them and their efficiency. A continuous- and an intermittent-HSSF (C-HSSF and I-HSSF) were stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 48 publications
0
5
0
1
Order By: Relevance
“…To remove colloidal particles that cause turbidity in water, size exclusion is utilized, which leads to the deposition of particles within the sand matrix. This deposition and subsequent decay of the organic matter it contains predominantly occur at the top of the sand bed, resulting in the formation of a biologically active surface layer called Schmutzdecke (Guchi, 2015;Lubarsky et al, 2022).…”
Section: Head Loss In the Slow Sand Filtermentioning
confidence: 99%
“…To remove colloidal particles that cause turbidity in water, size exclusion is utilized, which leads to the deposition of particles within the sand matrix. This deposition and subsequent decay of the organic matter it contains predominantly occur at the top of the sand bed, resulting in the formation of a biologically active surface layer called Schmutzdecke (Guchi, 2015;Lubarsky et al, 2022).…”
Section: Head Loss In the Slow Sand Filtermentioning
confidence: 99%
“…If these particles are composed of organic matter, they will further undergo biological decay. Particle removal occurs predominately at the top of the sand bed, in the surface layer known as the Schmutzdecke or biofilm layer [8,16]. Dissolved organic matter that enters the filter, or that is created from particle decay in the Schmutzdecke layer, can be mineralized lower in the filter.…”
Section: Mechanisms Of Pollutant Removalmentioning
confidence: 99%
“…Langenbach et al [60] found that slow sand filters removed E. coli and Enterococcus by 98.6-99.8% and 98.9-99.9%, respectively. On the surface of slow sand filters, a biofilm is formed, which has a biological activity and can therefore remove bacteria, organic matter, particles, and nutrients [61][62][63]. Sun et al [62] observed that slow filtration with aerobic heterotrophic biofilm exhibited higher removal of ARGs than slow filtration without any biofilm.…”
Section: Sand Filtrationmentioning
confidence: 99%